Optimized Configuration of a Hybrid PhotovoltaicWind System Integration - Anoune, Kamal; Laknizi, Azzeddine; Bouya, Mohsine; Astito, Abdelali; Ben Abdellah, Abdellatif (International Journal of Psychosocial Rehabilitation, 2020)
The Hybrid Photovoltaic-Wind System (HPWS) is becoming the most current renewable energy source used to power an electrical load demand. Hybridization helps to take all their advantages through reaching the best compromise between technical and economic criteria. In this paper, a thorough analysis of one-year weather situations and energy performance for two locations (Rabat and Tangier) is performed for sizing and integrating HPWS. The target is to find the optimized hybrid configuration capabilities to ensure the electrical load demand of the laboratory prototype. The TRNSYS/Matlab has been used to simulate the annual performance of different configurations of HPWS and provides the optimum configuration, which ensures supplying the load demand. Moreover, the analysis of the dynamic simulation results allows having visibility of the hybrid system requirement and the integration cost, besides evaluating the economic aspect of each optimized solution. The hybridization of two sources of energy can, in some cases, reduce the cost of installation and energy. As a result, for the same load profile and for two coastal sites spaced 250 km apart, two different system requirements have been identified: PV=9 kWp-Wind=1 kW for UIR Rabat and PV=3 kWp-Wind=3 kW for FST Tangier. And also two different capital costs have been found: €17215 for UIR Rabat and €14695 for FST Tangier.